Power Supply System In Smart House Modeling With Solar Cells - Agung Nendy H, Albertus (Sean Institute, 2023)
The development of science and technology is increasingly rapid, as are developments in the world of electronic technology. A lot of equipment that works with electronic systems. Solar cell technology is one of the technological developments. This solar cell technology is expected to reduce dependence on the provision of resources from the government. The solar cell system, which is equipped with an electronic system as a supporting device, such as detecting the position of sunlight and controlling battery charging, can increase the efficiency of the system's work. In this supply system using a Photovoltaic (PV) module. This solar cell will convert solar energy into electrical energy. This system is equipped with a battery charging system. This system is equipped with a light position detector. This light position detector will look for the origin of the light source, in this case the light source in question is sunlight. The solar cell will rotate according to the position of the light (in this case the light source is sunlight) with a light position detection device. This light position detector will rotate the solar cell from east to west and from north to south. The direction of rotation of this solar cell depends on the light source (the light source in this case is sunlight). As for this battery charging system, it will charge 12V batteries from solar cells. This light position detector will rotate the solar cell from east to west and from north to south. The direction of rotation of this solar cell depends on the light source (the light source in this case is sunlight). As for this battery charging system, it will charge 12V batteries from solar cells. This light position detector will rotate the solar cell from east to west and from north to south. The direction of rotation of this solar cell depends on the light source (the light source in this case is sunlight). As for this battery charging system, it will charge 12V batteries from solar cells.